Clinical Outcome of Superselective Transarterial Embolization for Acute Colonic Gastrointestinal Bleeding: A Retrospective Single-Center Experience - Rajendra Kumar Behera; Mohak Narang; Shivam Pandey; Kumble Seetharama Madhusudhan (Journal of Clinical Interventional Radiology ISVIR)
Objective The aim of the study was to assess the safety and efficacy of transarterial embolization in the treatment of acute lower gastrointestinal hemorrhage (LGIH) from colonic origin and to determine factors that influence the treatment outcome.